Local authorities as actors in the emerging "school-led" system in England. Issue 4 (7th June 2022) - Crawford, Megan; Maxwell, Bronwen; Coldron, John; Simkins, Tim
ABSTRACT: Most research to date about the English government's policy to make schools independent of local authorities (LAs) has looked at the "macro" level of national policy and at the "micro" level of the institution. The study of which this article is a part explores changes at the "meso" level of the locality. Over a period of six years, 52 semi-structured interviews were carried out with key actors at school, LA and local system levels in three areas. Participants were chosen purposively because of their key positions in the local schooling systems. The article focuses on the role of the LA as an actor in the "school-led" system and explores how LAs are repositioning their role and enacting influence in new ways. The article also discusses how changes in local arenas over time have been affected by the different responses to academisation of primary and secondary schools. The article uses an adaptive theory methodology to bring together theorising set out in earlier articles and theory generated by others, with theory generated from this new analysis.